Aerobic and anaerobic power distribution during cross-country mountain bike racing - Prinz, B.; Simon, D.; Tschan, H.; Nimmerichter, A. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine aerobic and anaerobic demands of mountain bike cross-country racing.